Kajian Bentuk Gerak dan Tujuan Serangan Silek Taralak di Perguruan Talago Biru Maninjau Kecamatan Tanjung Raya - Resha Gustina Putri; Indrayuda Indrayuda (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to describe the shape of the silek taralak movement in Maninjau, Tanjung Raya District. The type of research used is qualitative research with a descriptive method of analysis. The instruments used are their own lamps with supporting instruments such as stationery, cameras, and mobile phones. Data was collected by means of literature studies, observations, interviews, and documentation. The steps used to analyze the data are data collection, data reduction, data presentation, and conclusion drawn. The results show that Silek Taralak aims to create complete control over the opponent through fast, precise, and devastating attacks, by maximizing the impact on the vital areas of the opponent's body. Each attack technique in Silek Taralak is specifically designed to attack the vital parts of the opponent's body with the aim of disabling or controlling them. Attacks are generally focused on the heartburn, right rib, back, elbow, neck, and shoulder, using various techniques such as punches, locks, fractures, and slams. Techniques such as Elo suok and Masuak kida attack heartburn and ribs, while Ampai breaks the opponent's hands and elbows. There are also attacks that emphasize locks and slams, such as Tangkok smoked and Kungkuang karo, which lock the opponent's neck and hands before knocking them down or slamming them. In addition to offensive attacks, defensive techniques such as Tapiak raok and Gelek function to deflect the opponent's attacks, followed by effective counterattacks.